AIF1 Gene RS2269475:C>T Polymorphism is Associated With Rheumatoid Arthritis Development but not With Disease Activity - Andrzej PAWLIK,; Violetta DZIEDZIEJKO,; Mateusz KURZAWSKI,; Krzysztof SAFRANOW, (Archives of Rheumatology, 2015)
Objectives: This study aims to examine whether the allograft inflammatory factor-1 (AIF1) gene rs2269475:C>T polymorphism is associated with rheumatoid arthritis (RA) susceptibility, and whether this polymorphism influences disease activity in patients with RA. Patients and methods: We examined 380 patients (62 males, 318 females; mean age 58.1±12.9 years; range 20 to 78 years; age at disease onset 47.4±13.5 years) with RA diagnosed according to the criteria of American College of Rheumatology and 378 healthy control subjects (126 males, 252 females; mean age 69.6±12.1 years; range 21 to 75 years). Disease activity score in 28 joints (DAS28) was calculated. The active form of RA was diagnosed when DAS28 was >2.5, the non-active form was diagnosed when DAS28 was ≤2.5. Results: The frequency of TT genotype was significantly higher in RA patients compared with the controls (TT vs. CT+CC: odds ratio=6.22, 95% confidence interval: 1.82-21.28; p=0.0013). The frequency of T allele was 18.55% among RA patients and 12.04% among healthy subjects (odds ratio=1.67, 95% confidence interval=1.25-2.21; p=0.00046). There were no statistically significant differences in distribution of genotypes and alleles between patients with active and non-active disease (DAS28 >2.5 and ≤2.5, respectively). Conclusion: The results of present study suggest that AIF1 gene rs2269475 polymorphism is associated with RA development; however, has no influence on disease activity.